Organizational behavior management through group counseling discussions as a radicalism preventive effort - Dina Hajja Ristianti; Guntur Putrajaya; Irwan Fathurrochman (Jurnal Konseling dan Pendidikan)
Lembaga dakwah kampus (LDK) or Da’wah organization in campus as a student organization that concentrates on the Islamic teaching. This research uses a descriptive approach. In general, this study describes the behavior of radicalism and organizational behavior management among students of LDK members in IAIN Curup and the effect of group counseling activities on radicalism and organizational behavior management. To measure radicalism in this study is to use a closed questionnaire, the questionnaire was arranged based on the lattice that has been made based on theory by determining variables, sub variables and indicators of research. The researcher wanted to see the management of organizational behavior through the Group Counseling Disscussions as a radicalism preventive effort at Da’wah organization in IAIN Curup. Moreover, the findings show that, among the Da’wah organization’s members, radicalism it indicates that the behavior of radicalism in the category is quite radical. Group dynamics that occur in group counseling discussions are also good as seen from the enthusiasm and cohesiveness of students in discussions. The radicalism behavior and organizational behavior management before being given group counseling discussion activities are not the same as radicalism behavior and organizational behavior management after group counseling discussions.